Local Reference of splenic volume in Healthy Sudanese Subjects Sonographically - Yousef, Mohamed (British Journal of Healthcare and Medical Research, 2018)
This study was carried out to estimate normal linear dimensions and volume of the spleen in Sudanese using ultrasonography, and to keep it as standards reference for diagnostic purposes. This prospective study was done at Radiology Department, National Ribat University Hospital, Khartoum, Sudan, conducted on 108 volunteers (72 males and 36 females). All linear dimensions of spleen were measured, and splenic volume was calculated using ultrasonography. The splenic volume was then analyzed with age and body parameters using the Pearson’s correlation coefficient. Results of this study revealed that the mean values of the age, height, weight of subjects, spleen length (SL), spleen width (SW), spleen thickness (ST) and spleen volume were calculated were found to be 38.74±18.898years,163.11±17.747mm,65.33±15.431kg,91.07±11.330mm,37.59±7.440mm, 37.78±8.085mm and 70.63±31.924cm3 respectively. Age had no significant effect on spleen volume (p=0. 684). There was a significant positive correlation, using Pearson’s correlation coefficient, between the spleen volume, and other parameters (height p=0.000, and weight p=0.002. The present study concluded that a local reference of spleen dimensions was established with a different range of values reported previously.